A classification of the penial microsetae of Gonyleptoidea (Opiliones: Laniatores) - Kury, Adriano B. (Zootaxa, 2016)
The macrosetae of the ventral plate of Laniatores penis have been occasionally described and used for systematic purposes in the literature, to the point of having a whole system created for them in the recent study Of Kury & Villarreal (2015), in a paper where a phylogenetic analysis of the subfamily Gonyleptoidea was performed. Contrastingly, the microsetae of ventral plate of Gonyleptoidea are left undescribed in descriptive works, where the penis is often illustrated without a ventral view of the ventral plate. In some works with SEM images microsetae do appear, although they remain undescribed and/or unacknowledged (e.g., Townsend et al., 2010 figs 8–10; Coronato-Ribeiro & Pinto-da-Rocha 2015, where microsetae are visible in photos, but only barely mentioned). In the case of line drawings, exceptionally a few microsetae are shown mainly in the lateral view of the penis ventral plate (Acosta 2001, figs 17–21; Weber 1988, fig 6b). Exceptions to this treatment are Kury (2012: 41, figs 14–15) in which besides microsetae are illustrated their distribution pattern is described and Kury (2014), where even a subgroup of Gonyleptoidea was created and named—Microsetata—for species possessing a mat of microsetae on the ventral surface of ventral plate. Furthermore, among the characters used for the analysis in Kury & Villarreal (2015), the authors listed one containing five types of microsetae, which were not explained. Here, these types and their topology are described to make up for that omission.